Loose Parts: Stimulation of 21st Century Learning Skills (4C Elements) - Besse Nirmala; Suci Aprilyati Ruiyat; Haerul Annuar; Uswatun Khasanah5; Mochamad Sukardjo (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
There are many problems faced by teachers in stimulating children's development. One of them is the 4C skills. Teachers give more assignments contained in the Children's Worksheets, even though in the surrounding environment there are many materials that can be used as learning media. This study aims to develop a learning model by utilizing loose parts media to stimulate children's 4C skills. The type of research used is research and development adapted from Borg Gall, Dick, Carey, Carey, and Hannafin Pack. The research uses material expert validation, language, media, and learning design. Data collection techniques through observation, interviews, and documentation. The results of the study show that learning models using loose parts media can stimulate children's 4C skills. Aspects of critical thinking, when finding a problem, children can solve it by continuing to try. Creativity, children have the skills to think outside the box, try to assemble from various loose parts, develop ideas, and find new innovations. Collaboration, children can work together and quickly adapt to others. Communication, children can share thoughts, questions, ideas, and play experiences.